Elizabeth Wong, Karpal Singh and Hudud : can Pakatan survive differences? - Goh, Nur Firdaus Firoz (2009)
Since its success at the 8 March 2008 general election, Malaysia's opposition Pakatan Rakyat has seen challenges that often test the coaliton's fundamental differences. Can Pakatan stay glued and gain strength from these trials or will it give way to ideological differences?